Pelatihan Microsoft Office untuk Meningkatkan Keterampilan Digital Remaja di Desa Menceh - Fathurrahman, Imam; Usma Wardani, Iwan; Mu'Tashim, Aan; Pranata, Aditya; Maulidi, Dedi; Sholihah, Hikmatun; Sabirin Haris, M.; Zulkipli (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
In the digital era, the ability to operate office software such as Microsoft Office has become an essential need, including for the community of Menceh Village, East Lombok, who still face challenges in accessing technology and digital skills. With a population of 7,568, the majority being junior and senior high school students, limited facilities such as laptops and a lack of technological understanding hinder the learning process. Through the Microsoft Office training program (Word and Excel), the people of Menceh Village were given the opportunity to enhance basic computer skills, both to support formal education and to prepare for the workforce. Based on evaluations, this training successfully improved participants' abilities in creating school documents such as papers and proposals, as well as data management using Microsoft Excel. This program not only benefits the teaching and learning process but also equips participants with digital skills for a more competitive future.